1992
DOI: 10.1111/j.1365-3016.1992.tb00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Birth to ten: child health in South Africa in the 1990s. Rationale and methods of a birth cohort study

Abstract: Birth to Ten is a longitudinal birth cohort study which began in April 1990 in the Johannesburg/Soweto area of Transvaal, South Africa. In this paper, the reason for the initiation of the study and its location in the current sociopolitical context is discussed. The health status of South African children in terms of infant mortality, morbidity (notifiable diseases) and nutritional status is described and mention is made of measures of psychological health and the importance of environmental pollution on healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Details of the BTT study design have been reported elsewhere (29)(30)(31)(32)(33) but, in a brief, the BTT study commenced in 1990 as a 10-year cohort observational study designed to follow factors associated with the survival and health of some 2000 urban children from all the South African communities living in the Johannesburg/Soweto area of Gauteng Province. Details of the BTT study design have been reported elsewhere (29)(30)(31)(32)(33) but, in a brief, the BTT study commenced in 1990 as a 10-year cohort observational study designed to follow factors associated with the survival and health of some 2000 urban children from all the South African communities living in the Johannesburg/Soweto area of Gauteng Province.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the BTT study design have been reported elsewhere (29)(30)(31)(32)(33) but, in a brief, the BTT study commenced in 1990 as a 10-year cohort observational study designed to follow factors associated with the survival and health of some 2000 urban children from all the South African communities living in the Johannesburg/Soweto area of Gauteng Province. Details of the BTT study design have been reported elsewhere (29)(30)(31)(32)(33) but, in a brief, the BTT study commenced in 1990 as a 10-year cohort observational study designed to follow factors associated with the survival and health of some 2000 urban children from all the South African communities living in the Johannesburg/Soweto area of Gauteng Province.…”
Section: Methodsmentioning
confidence: 99%
“…Most longitudinal birth cohort studies enroll their participants at birth or soon after (e.g., Fergusson, 1998;McLanahan, et al, 2003;Yach et al, 1991). As all births in New Zealand are registered, enrollment at birth reduces difficulties with contacting prospective participants.…”
Section: Contacting a Diverse Population To Enable Antenatal Enrollmentmentioning
confidence: 99%
“…It is unlikely that we can ascribe these lower smoking rates purely to the students' medical training because it is generally recognised that an inverse relationship exists between general educational level and smoking and similar evidence can be found amongst other professionals (Yach et al, 1991). The percentage of medical students smoking cigarettes was similar to the findings of a study conducted with interns and residents in Ontario (Myers & Weiss, 1987) where 15,1% of males and 12,9% of females were smoking and lower than the figure of 21,4% obtained in a study of medical students in Haifa (Nachtigal, Rishpan & Epstein, 1989).…”
Section: Discussionmentioning
confidence: 91%